2017
DOI: 10.1002/chem.201704247
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of 6,6‐Disubstituted Pentafulvenes Containing a Chiral Pendant Hydroxy Group

Abstract: Simple enantioselective synthesis of 6,6-disubstituted pentafulvenes bearing chiral pendant hydroxy groups are attained by cascade reactivity using commercially available proline-based organocatalysts. Condensation of cyclopentadiene with the acetyl function of a 1,2-formylacetophenone, followed by cyclization of a resulting fulvene-stabilized carbanion with the formyl group, generates bicyclic chiral alcohols with initial er values up to 94:6. Exceptional enantio-enrichment of the resultant alcohols results u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…All other chemicals were purchased from ABCR, Acros, Alfa Aesar, Fluorochem, Merck, Sigma-Aldrich, and TCI Europe at highest commercially available purity and used without further purification. Compound 2b and 3b were prepared according to the procedures reported by Capitosti et al Compounds 8 , 13 , and 17 were prepared according to the procedures previously reported. Thin-layer chromatography (TLC) was performed on Merck silica gel 60 F 254 TLC aluminium sheets and visualized by ultraviolet light (254 nm) and/or with ceric ammonium molybdate, potassium permanganate, or ninhydrine staining solution. Flash column chromatography was performed on Acros silica gel 35–70, 60 Å, using a forced flow of eluent (method of Still).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…All other chemicals were purchased from ABCR, Acros, Alfa Aesar, Fluorochem, Merck, Sigma-Aldrich, and TCI Europe at highest commercially available purity and used without further purification. Compound 2b and 3b were prepared according to the procedures reported by Capitosti et al Compounds 8 , 13 , and 17 were prepared according to the procedures previously reported. Thin-layer chromatography (TLC) was performed on Merck silica gel 60 F 254 TLC aluminium sheets and visualized by ultraviolet light (254 nm) and/or with ceric ammonium molybdate, potassium permanganate, or ninhydrine staining solution. Flash column chromatography was performed on Acros silica gel 35–70, 60 Å, using a forced flow of eluent (method of Still).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Such conditions are indeed known to be beneficial for standard Knoevenagel reactions, , to which fulvene synthesis is closely related. Buffered media were also very recently successfully employed for the organocatalytic synthesis of chiral fulvenes. In this work, we demonstrate that it is indeed possible to significantly increase the formation rate of certain fulvenes by employing a pyrrolidine-buffered acetonitrile solution. A kinetic investigation of the catalyzed reactions of two different groups of substrates by NMR and UV–vis spectroscopy yielded a mechanistic model that rationalizes previous observations.…”
Section: Introductionmentioning
confidence: 71%
“…[5g] However, the use of this solvent might be limited by its higher cost than other typical organic solvents, and it also shows toxicity such as serious eye damage. We thus examined this reaction using catalyst 19 with a di ‐phenylmethanol moiety and related catalyst 20 with a mono ‐phenylmethanol moiety, in our identified superior i Pr 2 O solvent (entries 1 and 2, Table ). However, neither catalyst 19 nor catalyst 20 showed better catalytic activities than our 2‐azanorbornane catalyst 7 .…”
Section: Resultsmentioning
confidence: 99%